Diseño de una aplicación móvil enfocada en las normas de bioseguridad de la clínica odontológica de la universidad Antonio Nariño sede Cúcuta (2022)
Technological development work. A review of the literature was carried out in order to design a guide focused mainly on the biosafety manual of the dental clinic, subsequently, the mobile application interface was designed that illustrates the design of the application using 3 types of programmers: Fronted , Backed and Fullstack; Adobe Illustrator was used for the graphics and it was developed in the graphic environment of the Wix Web platform; Finally, a satisfaction survey is carried out on the users of the mobile application, evaluating its handling and functionality.